Життя та смерть Миколи Хвильового у світлі розсекречених документів ГПУ - Шаповал, Ю. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2008)
Based on the declassified documents of former Soviet secret services, the political and artistic activity of, a Soviet Ukrainian writer, Mykola Khvylovyi was investigated.